1797. Combining Rapid Diagnostics With Pharmacy Resident-Led Antimicrobial Stewardship to Optimize Outcomes for Bacteremia With Methicillin-Resistant S. aureus (MRSA-B), Methicillin-Susceptible S. aureus (MSSA-B), and Coagulase-Negative Staphylococcus (CoNS) at Yale New Haven Hospital (YNHH). (26th November 2018) - Bejou, Nika; McManus, Dayna; Peaper, David; Topal, Jeffrey
Abstract: Background: Given the severity of S. aureus bacteremia, prompt initiation of appropriate antibiotics is key. YNHH implemented the Cepheid ® Xpert MRSA/SA PCR in an effort to decrease the time needed to identify MRSA-B, MSSA-B, and CoNS. The impact of rapid diagnostics has been limited without stewardship or infectious disease involvement. Our unique notification algorithm utilized our on-call pharmacy residents to allow for 24/7 coverage. The primary objective was time to optimal antibiotic therapy (OAT) before and after implementation of the PCR and algorithm. Secondary outcomes included time to blood culture clearance (BCC), acceptance rate of pharmacist interventions, days of vancomycin therapy avoided, and 30-day mortality. Methods: A retrospective cohort study was conducted in adult inpatients with blood cultures positive for Gram positive cocci in clusters. The pre-implementation, control group (CG) included patients from April 2017 to October 2017 and the post-implementation, intervention group (IG) was from October 2017 to April 2018. Patients <18 years and polymicrobial bacteremia were excluded. Data collected in addition to primary and secondary outcomes included baseline demographics, allergies and empiric antibiotics. OAT included vancomycin for MRSA-B or MSSA-B with severe β-lactam allergy; nafcillin or cefazolin for MSSA-B; and discontinuation of vancomycin for CoNS deemed a contaminant. Results: Of the 544 patients reviewed, 434 met inclusion criteria: 182 in the CG and 252 in the IG with similar baseline characteristics. Mean time to OAT decreased from 10 hours in the CG to 5 hours in the IG ( P = 0.006). Time to BCC in the CG and IG cohorts decreased from 100 to 43 hours ( P = 0.0001). One day of vancomycin was avoided in patients with MSSA-B and 2 days with CoNS. 30-day mortality decreased from 18% ( n = 32) in the CG vs. 6% ( n = 15) in the IG ( P = 0.0001). Finally, 95% ( n = 153/161) of pharmacist interventions were accepted. Conclusion: Utilizing the on-call pharmacy resident for notification of rapid diagnostic results for S. aureus bacteremia, we saw a significant decrease in time to OAT, BCC, and 30-day mortality. Our study demonstrates that in the setting of limited stewardship resources, additional members of the healthcare team can be used to optimize antibiotics in conjunction with rapid diagnostics. Disclosures: All authors: No reported disclosures.